Public Television and the Ought of Public Policy - Sidney S. Alexander (Washington University Law Quarterly, 1968)
Will the American people find happiness in Public Television? Is Public Television in the public interest? In this Article, I argue that this subject is within the cognizance of the rational faculty; and neither does that faculty deal with it solely in the way of intuition. Considerations may be presented capable of determining the intellect either to give or withhold its assent to the doctrine.
Keywords: Public Television; morality